Determining Intention of Consumers to Purchase Electric Vehicles in Chongqing, China - Zhao, Biming (Scholar: Human Sciences, 2024)
Purpose: The primary objective of this research is to investigate the determinants that shape consumers’ purchase intention towards electric vehicles in the region of Chongqing. To achieve this, the study employs a conceptual framework encompassing several key factors including perceived benefit, perceived risk, attitude, environmental concerns, subjective norm, perceived behavioral control, and purchase intention. Research design, data, and methodology: This study employed a quantitative approach with a sample of 500 Chongqing residents aged 18 and above, holding driver’s licenses, and having sufficient income to consider electric vehicle purchases. The research instrument was validated using Item-Objective Congruence (IOC), and internal consistency was confirmed with Cronbach’s alpha. Various sampling techniques, including judgmental, quota, and convenience sampling, were used. Statistical analysis involved Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM). Results: Perceived benefit and perceived risk significantly influence attitude. Attitude, subjective norm, and perceived behavioral control are significant factors of purchase intention. Conversely, environmental concerns have no significant influence on purchase intention. Conclusions: Stakeholders can craft more effective strategies and policies to foster the adoption of sustainable transportation options in the region. Recommendation addresses a specific aspect of consumer decision-making and can collectively contribute to a more sustainable and environmentally friendly transportation future for the city.